Implementation of Policies for the Regulation of Street Vendors in Majalengka Regency - Aura Yulliananda Lesmana; Khaerudin Imawan; Leni Rohida (Pusat Publikasi Nusantara, 2026)
The Majalengka Regency Government issued Regent Regulation No. 12 of 2022 on the Management and Empowerment of Street Vendors. Street vendors play a vital role in the local economy. However, they often cause problems related to sanitation, the use of public spaces, and public order. The objective of this study is to examine Regent Regulation No. 12 of 2022, the factors influencing its success and obstacles, and the efforts undertaken by the Satpol PP Agency. This study employs a qualitative approach using a descriptive method. The findings indicate that the implementation of the Regent’s Regulation regarding street vendor management policies has not been effectively carried out; obstacles persist. Street vendors prioritize strategic locations and economic sustainability, while the government emphasizes public order and the function of public spaces. This policy benefits both the government and the broader community, particularly regarding public order. Vendors’ compliance with the policy is influenced by the social circumstances of street vendors and the lack of strategic relocation sites. This study concludes that the implementation of Regent Regulation No. 12 of 2022 still faces several challenges, particularly regarding support from the target group and the sustainability of vendors’ behavior. Therefore, it is crucial to enhance vendors’ involvement in the policy-making process, provide more representative spaces, and adopt greater accountability strategies to achieve the goal of fair and sustainable street vendor management.